Análise do comportamento de sistemas dinâmicos com absorsores de vibração não-lineares sintonizados - Marques Filho, Marcello Gomes (2022)
Slender and flexible structures, such as buildings or long span bridges, have become more susceptible to dynamic loads effects and an increment of their oscillation amplitudes can be noticed. Hence, the effect of large-amplitude vibrations and the consideration of nonlinearities become a relevant factor on the analysis, and, in a lot of cases, an intervention is necessary, by using vibration control mechanisms. First, in this work, the performance of a nonlinear tuned mass damper is evaluated when applied to a nonlinear Duffing equation considering nonlinear stiffness parameters with both softening and hardening behavior for the main system and the damper. For this, damped and undamped Duffing nonlinear oscillators are studied when subjected to a harmonic load or free vibration and attached to a nonlinear damper. First, the optimal linear control parameters were obtained by using Den Hartog’s criteria and these parameters are used to evaluate its performance on the nonlinear vibration regime. Then, the performance of a nonlinear tuned mass damper is evaluated when applied to a simply supported nonlinear 2D Euler-Bernoulli beam, subjected to a harmonic load or an aerodynamic follower load. For this case, the optimization process is also performed. A parametrical analysis is performance to evaluate the quality of the nonlinear tuned mass damper on the resonance curves, basin of attraction, time responses, phase planes and Poincaré sections for both the discrete and the continuous systems.